2003
DOI: 10.1002/jez.b.11
|View full text |Cite
|
Sign up to set email alerts
|

Expression of foreign genes in lamprey embryos: An approach to study evolutionary changes in gene regulation

Abstract: Evolution in development can be viewed as a sequence of changes in gene regulation. To investigate the cross-species compatibility of 5' upstream regulatory regions, we introduced exogenous gene constructs derived from a gnathostome genome into fertilized eggs of the Japanese lamprey, Lampetra japonica, a sister group of the gnathostomes. Eggs were injected with gene constructs in which a sequence encoding the green fluorescent protein (GFP) had been located downstream of either a virus promoter or 5' regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In the previous studies, we reported the regulatory function of upstream regions of striated muscle actin genes of the teleost, medaka Olyzias latipes (Kusakabe et al,'99a). These regions can activate transcription in skeletal and cardiac muscle cells when introduced into Lethenteron japonicum embryos (Kusakabe et al, 2003). Our results showed that the transcriptional regulatory mechanisms of striated muscle-specific actin genes are conserved between the lamprey and the medaka.…”
Section: Introductionmentioning
confidence: 61%
“…In the previous studies, we reported the regulatory function of upstream regions of striated muscle actin genes of the teleost, medaka Olyzias latipes (Kusakabe et al,'99a). These regions can activate transcription in skeletal and cardiac muscle cells when introduced into Lethenteron japonicum embryos (Kusakabe et al, 2003). Our results showed that the transcriptional regulatory mechanisms of striated muscle-specific actin genes are conserved between the lamprey and the medaka.…”
Section: Introductionmentioning
confidence: 61%
“…The 5′-flanking sequences of the medaka muscle actin genes are known to drive the expression of the reporter gene encoding green fluorescent protein (GFP) in the striated muscles of Japanese lamprey embryos [37]. These results imply that the 5′-flanking sequences of Japanese lamprey muscle-specific MYH s also drive the reporter gene expression in teleosts.…”
Section: Resultsmentioning
confidence: 99%
“…The results presented here suggest that considering the germline genome structure and how somatic changes alter this structure when using lamprey as a model for comparative developmental and genomic studies will be especially important. With ongoing progress toward complete sequencing of the lamprey somatic genome (21) and the recent development of several techniques for performing genetic manipulations of lamprey embryos (17)(18)(19)(20), we anticipate that the lamprey genome will prove fertile ground for identifying mechanisms that mediate the differential development of cell lineages and participate in large-scale rearrangement and stabilization of vertebrate genomes.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally validated computational screens for other germline-limited sequences uncovered several additional sequences that are lost during developmental restructuring of the lamprey genome, including one sequence that is homologous to SPOPL (speckle-type POZ protein-like) genes, which is transcribed in lamprey testes and lost during embryonic development. The presence of predictable and extensive reorganization events within the genome of the lamprey, coupled with its high fecundity (16) and amenable embryology (17)(18)(19)(20), present a uniquely tractable system for understanding the dynamics of genome stability and the consequences of reorganization in the context of ''normal'' vertebrate development and cell biology.…”
mentioning
confidence: 99%